Digital Transformation: Characteristics and Advantages of Its Teaching and Learning - Ibrahim Babakr Elhaj Abdelkader; Mohamed Hamed Mohamed Said; Rijal Mahdi (Diwan Media Pustaka, 2024)
Digital transformation in education has emerged due to technological advancements, significantly impacting teaching and learning processes. Initially focused on educational tools and materials, it has expanded to encompass digital technologies, becoming essential to educational strategies. This study examines the characteristics and benefits of digital transformation, specifically in language education. The objective is to explore how digital tools enhance the roles of teachers, students, and educational content, improving educational outcomes, particularly in Arabic language instruction. The research uses a library-based method, gathering data from various literature sources, including books, journals, and previous studies. It analyzes how digital transformation influences key elements of the educational process: the teacher, the learner, and the educational material. The results show that digital transformation improves teacher performance by increasing efficiency, enhancing teaching practices, and enabling better use of time and resources. It allows for more interactive, engaging content delivery and motivates students, fostering curiosity and participation. Students benefit from a more dynamic learning environment that strengthens their engagement and learning outcomes. Overall, digital transformation bridges the gap between traditional educational methods and modern approaches, enhancing the effectiveness of teaching and learning, especially in Arabic language education. It fosters a more interactive and efficient learning experience, improving educational results by engaging students and teachers.